Comparative study of inventory management and just-in-time tactics - Meon, Mohd Suhairil (2005)
This thesis is presenting a comparative study of inventory management system and just-in-time (JIT) tactics. Inventory management system always related to the efficient technique of storing the inventory. It has been practicing long time ago and still being used nowadays. Apart from that, JIT tactics is a quite new technique and it is a subset of lean manufacturing. Just-in-time (JIT) is a management philosophy that strives to eliminate sources of manufacturing waste by producing the right part in the right place at the right time. This thesis contains comparisons between inventory management system and JIT tactics, analysis of related costs and case study. It discussed on the differences of these two techniques in managing the inventory in term of lot sizes, layout, workforce, suppliers, scheduling and maintenance. Also, the comparison between Economic Order Quantity (EOQ) and Just-In-Time (JIT) is clearly being shown in this thesis.